2019
DOI: 10.1111/bld.12294
|View full text |Cite
|
Sign up to set email alerts
|

Self‐concept and facial appearance of individuals with an intellectual disability: A scoping review

Abstract: Accessible Summary• This paper looks at how self-concept is related to facial appearance.• Very little information can be found on how persons with intellectual disabilities think and feel about their own facial appearance.• In this review 19 articles on subject of self-concept in people with intellectual disabilities were included.• Results show that self-concept of individuals with intellectual disabilities is affected by the relationships they have (positively and negatively).• The perceptions of caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A total of 213 authors' keyword was identified. The most frequent keywords were oral health (9), autism (7), down syndrome (6), dental caries (6), children (6), caries (5), dental care for disabled (5), dental education (5), down's syndrome (5) and periodontal disease (5). Figure 2 present a network analysis of the co-occurrence of the keywords across the years showing the switch of patterns throughout the years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 213 authors' keyword was identified. The most frequent keywords were oral health (9), autism (7), down syndrome (6), dental caries (6), children (6), caries (5), dental care for disabled (5), dental education (5), down's syndrome (5) and periodontal disease (5). Figure 2 present a network analysis of the co-occurrence of the keywords across the years showing the switch of patterns throughout the years.…”
Section: Methodsmentioning
confidence: 99%
“…The authors of a scoping review found no article about how individuals with intellectual disabilities perceived their appearance. 5 This gap in the literature needs to be further explored to improve the quality of life of these individuals. Since people with disabilities represent an important and growing group of individuals in the world, with almost a billion adults living with some type of disability 6,7 it is required that research and education on this topic need to grow and focus on how to prevent and combat inequalities on health access.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that VPA negatively predicted SC in children and adolescents with IDs during the COVID-19 pandemic. The predictive effects could be explained by social comparison leading to social stigma and negative SC in adolescents with IDs (Chien et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The integration of individuals with ID might be hindered by their self-perception (e.g., selfconcept) [9]. Shame, for instance, is a commonly reported experience, which is characterized by feeling inferior, worthless, devalued, or undesirable [10,11].…”
Section: Introduction 11 Intellectual Disabilitiesmentioning
confidence: 99%